Radio‐responsive tumors exhibit greater intratumoral immune activity than nonresponsive tumors. Issue 10 (11th November 2013) - Gerber, Scott A.; Lim, Joanne Y.H.; Connolly, Kelli A.; Sedlacek, Abigail L.; Barlow, Margaret L.; Murphy, Shawn P.; Egilmez, Nejat K.; Lord, Edith M.
<x xml:space="preserve">Abstract</x> Radiation therapy (RT) continues to be a cornerstone in the treatment for many cancers. Unfortunately, not all individuals respond effectively to RT resulting clinically in two groups consisting of nonresponders (progressive disease) and responders (tumor control/cure). The mechanisms that govern the outcome of radiotherapy are poorly understood. Interestingly, a new paradigm has emerged demonstrating that the immune system mediates many of the antitumor effects of RT. Therefore, we hypothesized that the immune response following RT may dictate the efficacy of treatment. To examine this, we developed a tumor model that mirrors this clinically relevant phenomenon in which mice bearing Colon38, a colon adenocarcinoma, were treated locally with 15Gy RT resulting in both nonresponders and responders. More importantly, we were able to distinguish responders from nonresponders as early as 4 days post‐RT allowing for the unique opportunity to identify critical events that ultimately determined the effectiveness of therapy. Intratumoral immune cells and interferon‐gamma were increased in responsive tumors and licensed CD8 T cells to exhibit lytic activity against tumor cells, a response that was diminished in tumors refractory to RT. Combinatorial treatment with RT and the immunomodulatory cytokine IL‐12 resulted in complete remission of cancer in 100% of cases compared to a cure rate of only 12% with RT alone. Similar data were obtained when IL‐12 was delivered by microspheres. Therefore, the efficacy of RT may depend on the strength of the immune response induced after radiotherapy. Additionally, immunotherapy that further stimulates the immune cells may enhance the effectiveness of RT.